(untitled) (Journal of Scientific Research, 2011)
The structural and electronic properties of 3’(4-(5-oxo-5-piperidin1-1-yl)penta-1,3-dienyl)benzo[d][1,3]dioxol-2-yl]-thymidine molecule have been investigated theoretically by performing density functional theory (DFT/3-21G*, 6-31G* and 6-31G**). The geometry of the molecule is optimized, and the electronic properties and relative energies of the molecules have been calculated by density functional theory in the ground state. The resultant dipole moments of the studied molecule are about 5.5, 6.36 and 7.35 Debyes by three levels (3-21G*, 6-31G* and 6-31G**, respectively). This property makes it an active molecule with its environment that is this molecule may interacts with its environment strongly in solution. Keywords: 3’-Azido-3’-deoxythymidine (AZT); Piperine; Density functional theory (DFT); Thymidine. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.6364 J. Sci. Res. 3 (2), 339-345 (2011)